Mechanisms of Chaperones as Active Assistant/Protector for Proteins: Insights from NMR Studies. Issue 4 (21st February 2020) - Hu, Yunfei; Li, Conggang; He, Lichun; Jin, Changwen; Liu, Maili
Abstract : Molecular chaperones are diverse families of proteins that play key roles in protein homeostasis. They assist the folding of client proteins or prevent them from irreversible aggregation under stress conditions. Diverse chaperone families contribute to different aspects of protein homeostasis by interacting with a wide range of client proteins. Despite the vital roles of chaperones in cell survival, the molecular mechanisms underlying chaperone functions remain elusive, due to the non‐specificity of chaperone‐client interactions and the intrinsic flexibility of the clients. Our understanding of the chaperone functional mechanisms, especially regarding chaperone‐client interactions, has greatly expanded in recent years, thanks to the significant contribution from various NMR studies. Solution NMR methods have unique advantages in characterizing disordered protein structures, detecting weak and non‐specific interactions, and probing conformational dynamics of proteins and protein complexes, etc ., and therefore are especially powerful in the studies of chaperone structure‐function relationships. In this review, we summarize some of the current knowledge of molecular chaperones, with emphasis on common features of chaperone‐client interactions and examples on a number of specific systems in which solution NMR methods were used to provide essential insights into their functional mechanisms. Abstract : Solution NMR methods provide various means for studying the structures, interactions and dynamics of chaperone‐client complexes.